3D‐printed Portable Platform for Mechanized Handling and Injection of Microvolumes Coupled to Electrochemical Detection. Issue 4 (23rd January 2019) - Mendonça, Dianderson M. H.; Rocha, Diego P.; Dutra, Gustavo S. V.; Cardoso, Rafael M.; Batista, Alex D.; Richter, Eduardo M.; Munoz, Rodrigo A. A.
Abstract: We present a low‐cost mechanized system fabricated using fused deposition modelling 3D‐printing technology to manipulate microvolumes and perform injections on an electrochemical cell in wall‐jet configuration. As a proof‐of‐concept, the amperometric detection of paracetamol (model analyte) on a screen‐printed electrode using 0.5 μL aliquots resulted in highly reproducible responses (RSD <3 %). Moreover, handling of microliter aliquots of butylhydroxytoluene (phenolic antioxidant) and 2, 2‐diphenyl‐2‐picrylhydrazyl (DPPH) to promote the radical‐scavenging reaction to determine antioxidant capacity by electrochemical detection of residual DPPH was demonstrated (time‐controlled reaction). A final application of the system was devoted to the analysis of cocaine and a common adulterant found in seized samples. The mechanized 3D‐printed analytical platform is capable to execute diverse sample preparation steps on board by handling microliter aliquots and subsequent electrochemical detection. 3D‐printing technology enabled the fabrication of a versatile and low‐cost (<U$200) mechanized system accessible to general chemistry labs. Abstract :